Perancangan UI Karya Duta Education Bandung Berbasis Website - Yan Septyunus Simbolon; Rita Komalasari (SisInfo, 2024)
In the context of modern education, efficient management of enrollment data is crucial for educational institutions. As a progressive educational institution, Karya Duta Education introduces innovation by implementing an online registration system. Currently, the institution or admin has difficulty recapping new student data due to the absence of an admin website provided by the institution. Admins still recap data manually in recapitulating new student data. However, to support the success of this implementation, it is necessary to design an optimal user interface (UI) for the admin panel. This study aims to design an efficient and intuitive UI for the online registration admin panel at Karya Duta Education. They are using the Design Thinking method. Modern UI design principles and best practices in user experience are applied to ensure smooth management of enrollment data. This UI design is expected to speed up the registration administration process, increase efficiency, and reduce the potential for human error. Thus, a well-designed online enrollment administration system will be the foundation for Karya Duta Education to provide more responsive and quality education services to prospective students.